O48 Novel interactions between bacterial strains and mucosal immune profiles after FMT for UC: STOP-colitis results. (19th June 2022) - Quraishi, Nabil; Quince, Christopher; Hewitt, Catherine; Beggs, Andrew; Gerasimidis, Konstantinos; Sharma, Naveen; Oo, Ye H; Hawkey, Peter; Ives, Natalie J; Manzoor, Susan; Loman, Nicholas; Hansen, Richard; et al.
Abstract : Background: Faecal microbiota transplantation (FMT) demonstrates therapeutic potential in ulcerative colitis (UC). Through a prospective, open-label randomised trial (STOP-Colitis pilot) we examined mechanistic insights associated with clinical response to FMT in UC. Methods: Thirty adult participants with active UC were randomised to either colonic (n=14) or nasogastric (n=16) route of administration of 8 FMT infusions over 8 weeks. Each patient was matched to an FMT donor. Changes in faecal microbial diversity and composition before/after FMT were analysed with shotgun metagenomics. Stool metabolomics analysis and mucosal immune cell phenotyping was performed. Correlation was evaluated with Kendall's Tau coefficient. Results: Eleven of the 20 patients completing the study achieved a clinical response to FMT. Response to FMT was associated with an increase in alpha diversity (P<0.005) and lower faecal calprotectin compared to non-responders. A negative association between calprotectin levels and alpha diversity was observed (P<0.005). Operational taxonomic units belonging to Clostridia deriving from the Christensenellaceae and Lachnospiracae families correlated with both reduced calprotectin and had high engraftment frequency (FDR adjusted P<0.10). In a cohort of patients with mucosal immune cell phenotyping, faecal metagenomic analysis revealed that multiple species belonging to Lachnospiraceae, Butyricicoccaceae and Oscillospiraceae families correlated positively with gut homing Tregs and negatively with Th17 cells (FDR adjusted P<0.10). Th17 cells positively correlated with flagellar adhesion and virulence pathways. Stool metabolomics analysis revealed a significant increase in butyrate following FMT however this did not correlate with response. Conclusion: We demonstrate significant correlations linking response to FMT and mucosal immunoregulatory shifts with changes in gut microbial diversity and key microbial species (short chain fatty acid producers) in patients with UC.